Novel ultrashort-acting benzodiazepine remimazolam lowers shivering threshold in rabbits - Muroya, Kenji; Ueda, Kenta; Wada, Keiichi; Kotoda, Masakazu; Matsukawa, Takashi (Frontiers in Pharmacology, 2022)
Shivering after surgery or during therapeutic hypothermia can lead to serious complications, such as myocardial infarction and respiratory failure. Although several anesthetics and opioids are shown to have anti-shivering effects, their sedative and respiratory side effects dampen the usefulness of these drugs for the prevention of shivering. In the present study, we explored the potential of a novel ultrashort-acting benzodiazepine, remimazolam, in the prevention of shivering using a rabbit model of hypothermia. Adult male Japanese white rabbits were anesthetized with isoflurane. The rabbits received either saline (control), remimazolam (either 0.1 or 1 mg/kg/h), or remimazolam + flumazenil, a selective γ-aminobutyric acid (GABA) type A receptor antagonist (n = 6 each). Thirty minutes after discontinuation of the drugs, cooling was initiated by perfusing 10 °C water via a U-shaped plastic tube positioned in the colon until the animal shivered. Core body temperature and hemodynamic and physiological parameters were recorded. Remimazolam at 1 mg/kg/h significantly lowered the core temperature change during shivering (-2.50 ± 0.20 °C vs. control: -1.00 ± 0.12 °C, p = 0.0009). The effect of 1 mg/kg/h remimazolam on the core temperature change was abolished by flumazenil administration (-0.94 ± 0.16 °C vs. control: -1.00 ± 0.12 °C, p = 0.996). Most of the hemodynamic and physiological parameters did not differ significantly among groups during cooling. Remimazolam at a clinically relevant dose successfully suppressed shivering in rabbits via the GABA pathway even after its anesthetic effects likely disappeared. Remimazolam may have the potential to prevent shivering in patients undergoing surgery or therapeutic hypothermia.